Modelling plant growth and development - Charles-Edwards, D. A. (Academic Press, 1986)
This timely text describes the physiological components, and models of them, of growth determiants defined in Physiological Determinants of Crop Growth by D.A. Charles-Edwards ( Academic Press). It extends the original analysis of dry matter production to encompass the morphological and phenological development of the plant. It uses the framework provided by the defined physiological determinants of growth as a vehicle to integrate knowledge of basic plant processes ( leaf growth, phyllotaxis, flowering, etc.) into an understanding of whole plant performance. Mathematics, mostly simple algebra, is used to formalise and quantify the relationships between the different plant processes. -- Back Cover.